Utility of Dendrochronology Crossdating Methods in the Development of Arctic Coralline Red Algae Clathromorphum compactum Growth Increment Chronology for Sea Ice Cover Reconstruction - Leclerc, Natasha; Halfar, Jochen; Porter, Trevor J.; Black, Bryan A.; Hetzinger, Steffen; Zulian, Meghan; Tsay, Alexandra (Frontiers in Marine Science, 2022)
Paleoclimate and paleoenvironmental reconstructions from increment-yielding archives strongly depend on precise age models. Like bivalves, corals, trees, and speleothems, the coralline alga Clathromorphum compactum produces annual growth increments and shows considerable promise as an environmental archive for arctic and subarctic regions. Though their growth increment widths correlate with temperature and sea ice cover in high Arctic regions, existing timeseries have not been crossdated. In fact, previous studies have shown a lack of inter-sample correlation in non-crossdated timeseries suggesting possible age model dating errors. Here, we use dendrochronology crossdating techniques and COFECHA software to ensure and validate synchrony between C. compactum timeseries (<141 years) from three specimens collected near Beechey Island, Nunavut, Canada. Results showed that non-crossdated timeseries constructed by four coralline red algae researchers using annual increments of the same C. compactum samples were highly variable and showcase the likelihood of dating errors in non-crossdated timeseries. Crossdating improved inter-series correlations, and correlations to sea ice-related records, suggesting that at least three crossdated timeseries are required to isolate paleoclimate signals. Our findings suggest that future reconstructions with C. compactum should employ crossdating techniques to reduce dating errors and allow for more precise climate reconstructions.